Skeletal muscle damage repair and adaptation to uphill and downhill running in humans - Krafft, Ingrid (My University, 1994)
Extensive disruption of muscle fibres has been shown to occur after short term eccentric exercise where high mechanical forces are generated. This study tested whether downhill running acts as a stimulus for inducing eccentric damage, and results in greater muscle damage and deterioration in muscular performance than an equal workload of uphill running. The study aimed at determining whether an adaptation or training eflect takes place such that the muscle is more resistant to the damaging effects of a repeated bout of the same exercise. In addition, the study aimed at determining whether the lower muscle volumes and forces of muscular contractions in females compared to males, makes females less susceptible to the damaging effects of eccentric contraction.
A Dissertation Submitted to the Department of Physiology, University of the Witwatersrand, Johannesburg for the Degree of Master of Science.
Keywords: Biological Transport, Active; Muscle, Skeletal; Human